Loop Electrosurgical Excision Procedure Instead of Cold-Knife Conization for Cervical Intraepithelial Neoplasia in Women With Unsatisfactory Colposcopic Examinations: A Systematic Review and Meta-Analysis. Issue 2 (April 2017) - El-Nashar, Sherif A.; Shazly, Sherif A.; Hopkins, Matthew R.; Bakkum-Gamez, Jamie N.; Famuyide, Abimbola O.
Abstract : Objectives: This meta-analysis compared loop electrosurgical excision procedure (LEEP) with cold-knife conization (CKC) for treating cervical intraepithelial neoplasia (CIN) in patients with unsatisfactory colposcopic examinations. Material and Methods: A literature search on MEDLINE, EMBASE, Cochrane Systematic Reviews, CENTRAL, Web of Science, and Scopus databases was conducted from inception until April 2015. We included clinical trials and cohort studies comparing CKC with LEEP for treating CIN. The primary outcome was a combined end point of persistent CIN (<6 months after conization) and recurrent CIN (>6 months). Secondary outcomes included procedural, pathologic, and long-term outcomes. Pooled relative risk (RR) and weighted mean difference (WMD) were used to report binary and continuous outcomes, respectively. Results: Among 26 studies, the incidence of persistent and recurrent disease after LEEP was comparable with that after CKC (15.6% vs 7.38%; RR = 1.35; 95% CI = 1.00–1.81). Loop electrosurgical excision procedure was faster, caused less intraoperative bleeding, and resulted in shorter hospital stay (WMD, 9.5 minutes [95% CI = 6.4–12.6 minutes]; WMD, 42.4 mL [95% CI = 21.3–106 mL]; and WMD, 1.5 days [95% CI = 1.1–1.8 days], respectively). Loop electrosurgical excision procedure cones were shallower with overall less volume and weight than CKC (WMD, 5.1 mm [95% CI = 3.2–7.1 mm]; 2.6 mm 3 [95% CI = 0.6–5.7 mm 3 ]; and 2.6 g [95% CI = 1.4–3.7 g], respectively). During follow-up, LEEP was associated with less cervical stenosis and fewer unsatisfactory examinations; however, this was not statistically significant (RR, 0.5 [95% CI = 0.1–1.5]; RR, 0.7 [95% CI = 0.4–1.2], respectively). Conclusions: Loop electrosurgical excision procedure is an acceptable alternative to CKC in women with CIN and unsatisfactory colposcopic examinations. Close follow-up is necessary for prompt detection and treatment of persistent or recurrent disease. Abstract : Loop electrosurgical excision procedure is an acceptable alternative to cold-knife conization in women with cervical intraepithelial neoplasia and unsatisfactory colposcopic examinations. Supplemental digital content is available in the text.